Quantification of weekly strength-training volume per muscle group in competitive physique athletes - da Silveira, Thiago Beraldo; de Almeida, Gustavo Paula Leite; Junior, Nelson Carvas; Machado, Alexandre Fernandes; Rica, Roberta Luksevicius; Pontes, Francisco Luciano; Scartoni, Fabiana Rodrigues; Bullo, Valentina; Gobbo, Stefano; Bergamin, Marco; Bocalini, Danilo S.; Figueira Júnior, Aylton; et al. (Frontiers in Sports and Active Living, 2025)
The purpose of the study was to quantify and compare the volume of training performed by competitive physique athletes, obtaining unprecedented findings at this level of specificity given the scarce specific literature and comparing with guidelines, in order to generate more specific and accurate conducts in the future. MethodsOne hundred and fifty-four athletes from different federations and categories were analyzed using questions with items about training strategies describing them and subsequently comparing them with each other and with guidelines.ResultsMany of the categories reduced training volume in pré-contest for most muscle groups. There is a variation in the average number of workouts per week between the off-season and the pré-contest period in different muscle groups. There was a significant difference in the weekly sets volume in categories (p < 0.05, α = 0,05): Men's Physique (MP) reduced (pectoral); Classic Physique (CP) and MP reduced (deltoids); Bodybuilding Classic (BC) vs. MP (pectoral) off-season and BC vs. MP (deltoids) off-season; Master (MT) increased (quadriceps); BC and MT increased (abdominals); CP vs. MP pré-contest (triceps surae). There was a significant increase in the duration of cardio work in pré-contest: CP, BC, Bikini (BK), and Wellness (WL) (p < 0.05, α = 0,05). An increase was observed as statistically significant in the weekly frequency of BC and Senior (SN) (p < 0.05). In most cases, there was an increase in the amount of cardio work during the pré-contest period.ConclusionNotable reductions in training volume were observed during the pré-contest period for some muscle groups. Both men and women exhibited a decrease in exercise frequency for some muscle groups during pré-contest, alongside an increase in cardio training. We suggest new studies that can help with developing more detailed training practices for physique athletes.